Pusa Prateek – A high yielding nutrientrich improved variety of tropical carrot - Kalia, Pritam; Sureja, Amish K; Saha, Swati; Singh, Shrawan; Tomar, B S (Indian Horticulture, 2026)
Pusa Prateek (IPC-3) is a high-yielding, nutrient-rich tropical carrot variety developed for cultivation during the rabi season in Zone VI (Rajasthan, Gujarat, Haryana, Delhi) and Zone VIII (Karnataka, Tamil Nadu, Kerala, Puducherry). The variety produces narrow, obtriangular roots with a small self-coloured red core, high carotenoids, lycopene, β-carotene and TSS content. It matures in 85–90 days and has an average yield of 30–32 t/ha, which is approximately 19% higher than the national check Pusa Rudhira. Pusa Prateek is suitable for salad, juice, cooking and halwa preparation, offering both enhanced farmer returns and nutritional benefits to consumers.